Characterization and comparison of Campylobacter bacteriophages - Al Kandari, Sharifa (2013)
Members of the genus Campylobacter are a major cause of food-borne disease worldwide. They can colonize the intestinal mucosa of poultry, to high levels leading to contamination of meat, at slaughter. Their numbers can be reduced in different ways including chicken treatment with bacteriophages. For such treatments to be successful, in depth understanding of the bacteriophage that infects and kills campylobacters is vital. The work in this thesis describes: isolation and comprehensive characterisation of bacteriophage candidates for future therapy applications.